Implikasi Bimbingan Kelompok tentang Dampak Aplikasi Tiktok terhadap Kepercayaan Diri Remaja - Nurussakinah Daulay; Anggreini Ayu Lestari Br Sembiring; Ayu Landa Fitri; Azura Mahyuliza Sembiring; Muhammad Ikhsan Fahmi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2023)
The number of users of the Tik Tok application in Indonesia is currently more than 30 million. Not only among adults, teenagers and even children already have the Tik Tok application on their gadgets. The TikTok application is now not only entertainment for its users, TikTok is also a source of income for many people. TikTok has a very big influence on its users, it can even change the pattern of life, character and also the daily life of each person so that it can have a positive or negative impact, especially on teenagers who are in the phase of finding their identity. Therefore, the authors conducted research to be able to find a solution to this problem. The purpose of this study was to find out in depth the impact of the TikTok application on adolescents in Timbang Lawan village and the effect of group guidance on the positive and negative impacts of the TikTok application. The research method used is qualitative research with a descriptive approach. The subjects in this study involved 8 informants who participated in group guidance services. The data in this study were collected through observation and interview techniques. After the group guidance was carried out, it was seen that there was a change in attitudes and habits of teenagers to be more productive than before after knowing the impact of using the TikTok application. Keywords Application, Impact, Character, TikTok